Some characteristics and functional properties of Chunma (Gastrodia elata) as a food supplement: a short review - Jaswir, Irwandi; Octavianti, Fitri; Lestari, Widya; Hendri, Ridar; Ahmad, Hasna (Faculty of Food Science & Technology, Universiti Putra Malaysia (UPM), 2017)
Gastrodin elata blume (Tianma in Chinese, Chunma in Korean) is a perennial parasitic herbaceous plant native to Korea, Japan and China (Chae et al., 2008). The plant has recently received very good attention, especially in Korea, due to its excellent health-promoting properties. This plant is reported to have excellent antioxidant, anticancer and anti-inflammatory properties. This paper briefly reviews some characteristics and functional properties of Chunma.